2012
DOI: 10.1161/circulationaha.112.094524
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-101 Inhibited Postinfarct Cardiac Fibrosis and Improved Left Ventricular Compliance via the FBJ Osteosarcoma Oncogene/Transforming Growth Factor-β1 Pathway

Abstract: Background-Cardiac interstitial fibrosis is a major cause of the deteriorated performance of the heart in patients with chronic myocardial infarction. MicroRNAs (miRs) have recently been proven to be a novel class of regulators of cardiovascular diseases, including those associated with cardiac fibrosis. This study aimed to explore the role of miR-101 in cardiac fibrosis and the underlying mechanisms. Methods and Results-Four weeks after coronary artery ligation of rats, the expression of miR-101a and miR-101b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
217
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(229 citation statements)
references
References 39 publications
10
217
1
1
Order By: Relevance
“…The infarct size after 24 hours of MI was decreased to 32.5±3.0% ( P <0.05) in AAV‐shTGFβR3 mice (Figure 7C). We examined the heart function after 4 weeks of MI because several reports have shown that the muridae ischemia heart shows characteristics of heart failure at this time point 5, 17. Fractional shortening and ejection fraction were significantly improved in AAV‐shTGFβR3 mice compared with AAV‐scramble mice (Figure 7D and 7E).…”
Section: Resultsmentioning
confidence: 98%
“…The infarct size after 24 hours of MI was decreased to 32.5±3.0% ( P <0.05) in AAV‐shTGFβR3 mice (Figure 7C). We examined the heart function after 4 weeks of MI because several reports have shown that the muridae ischemia heart shows characteristics of heart failure at this time point 5, 17. Fractional shortening and ejection fraction were significantly improved in AAV‐shTGFβR3 mice compared with AAV‐scramble mice (Figure 7D and 7E).…”
Section: Resultsmentioning
confidence: 98%
“…Anti-fibrotic action of miR-101a was mimicked by silencing c-Fos using siRNA, whereas effect of miR-101a in cultured CFs was cancelled by enforced expression of the c-Fos. In rats with chronic MI, four weeks after overexpression of miR-101a using adenovirus, remarkable improvement in cardiac performance was observed as well as reduction in interstitial fibrosis and inhibition of c-Fos and TGF-β1 expression [50] . Pioglitazone was further shown to increase miR-711 expression and significantly reduce collagen-Ⅰ levels similar to CFs, and overexpression of miR-711 suppressed collagen-Ⅰ levels.…”
Section: Mir-34a and Apoptosismentioning
confidence: 98%
“…At the moment, there is no data available from clinical trials evaluating the therapeutic clinical deployment of miRNAs in CVD. In vitro studies and animal models, though, have produced promising results with potential for a future clinical application [144][145][146][147][148]. Here, we provide an example on how miRNAs could effectively and useful be applied in a clinical setting:…”
Section: Mirnas -Therapeutic Applicationmentioning
confidence: 99%